La scimmia visuale. Immagini mentali, cave art e retroazione mediale - Parisi, Francesco (Scenari, 2021)
The purpose of this essay is trying to demonstrate that technology is not, as it is usually conceived, a product of our intelligence, but that the opposite is true: namely, that human intelligence is a product of technology. Following the ideas proposed by Radical Embodied Cognition and Material Engagement Theory, I will try to show why the concepts of mediation and media retroaction are useful if we want to understand how technologies exert their influence on us. Particularly, the aim of the paper is to present pictures as a case study, by exploring how cave art might have contributed to the onset of the modern representational human abilities. In other words, Homo sapiens does not have the ability to paint because he can create images in his mind, if anything, he can create such pictures because he has been learning to paint over the course of his evolution.